Unexplored dimensions Karl Menger on economics and philosophy (1923-1938) - Becchio, Giandomenica (Advances in Austrian economics ;, 2009)
Karl Menger (1902-1985) was the mathematician son of the famous economist Carl Menger. He was professor of geometry at the University of Vienna from 1927 to 1938. During that period, which was crucial from an historical and philosophical point of view, he joined the Vienna Circle and founded his Mathematical Colloquium. The present volume of Advances in Austrian Economics offers the transcription of those unpublished parts of Menger's notes written between 1923-1938. It is hoped that these notes, together with the editor's contextual explanations, provide a subtext to Menger's biography during this influential period.